Chronicle of a Momentaneous Success. Entertainment and Consumer Goods in Antenna 3’s Early Stage (1977-82) - Rossi, Emiliano (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This contribution explores the pivotal role of advertising in shaping the identity, programming, and sustainability of Antenna 3, a Lombard broadcaster active during the early years of Italian private television (1977-1982). Drawing on the ATLas research project and the channel’s partially digitised corporate archive, it examines the dynamic relationship between entertainment content and in-house advertising strategies. Antenna 3’s commercial model fostered innovative forms of brand integration and sponsorship which seem to anticipate today’s practices of product placement and branded content. A selection of key programmes illustrates how commercial messages were embedded in game shows, comedy, and variety formats, reflecting broader shifts in consumer culture and the rise of mass-market goods. The analysis also highlights the channel’s role in giving cultural visibility to Italy’s provincial areas, offering a dreamlike vision of modern consumerism. Finally, the study reflects on the challenges of cataloguing commercially dense TV content and underscores the importance of archival transparency. Advertising emerges not only as an economic driver, but also as a creative and cultural force central to understanding the most artisanal and experimental phase of local broadcasting in Italy.